Florística, fenologia e biologia floral da comunidade de uma ilha de mata de galeria inundável em Uberlândia - Resende, Isa Lucia de Morais (2003)
In the period of January to December of 2001 the floristic survey, the flowering and fructification phenology were accomplished, as well as the floral biology of the species of a floodedable gallery forest in Uberlândia, MG. The specimens in reproductive stadiums were collected, with the habit registration and occurrence place along the seven trails. These were open in the perpendicular forest to the Córrego Cabeceira of Lageado, in your left margin, and distended 40 m one of the other. The phenological survey had qualitative focus, enrolling the presence of buttons, flowers and / or fruits. To test the relationship among the number of species in each phenofase and the climatic variables in the same period the correlation of Spearman was used (rs). The flowers of the found species were analyzed with relationship to the foliowing aspects: color, scent presence, size, type morphological, offered resource and visitors. 105 species were registered, distributed in 87 genera and 49 families. The richest families were Rubiaceae, Asteraceae, Melastomataceae, Lauraceae, Orchidaceae and Piperaceae, representing about 40% of the total of registered species. The likeness floristic relatively low with other gallery forests it points out the importance of the adjacent vegetation and of the environmental heterogeneity that interferes in the composition floristic of these forests. Along the whole year species were registered with flowers and fruits. About 40% they bloomed for one or two months and the others for higher period to three months. A great number of species (52,8%) presented fructification with duration of one to five months. There was predominance of flowers clear, small, with resource of the type néctar, systems of pollination entomophily with prevalence of bees and with a variation in equilibrate proportions in the floral types opened and closed.